Social Justice for the Indigenous People of Penajam Paser Utara in the Era of IKN Development: Legal Analysis and Its Impact on Collective Rights and Its Impact on Collective Rights - Zuni Khusniyah; Nabila - (RESPONSIVE LAW JOURNAL, 2025)
This study aims to explore the application of the principle of social justice in the development of the new capital city IKN towards the collective rights of indigenous peoples, as well as the legal challenges they face in defending their rights during the development process. The research amploys by the qualitative approach, with the data collected from litelature studies. The data include books, articles journal scientific, news, studies academic, official website governmen, and others reference relevant. In the process of writing and discussing in this academic is used descriptive analytical method. The findings of this research is development of the National Capital City (IKN) in North Penajam Paser can bother rights collective public customs in the environment. These impact include the loss of customary land, neglect of culture local, and social injustice consequence from the lack of involvement public custom in the planning and development process. Research results This can used as base for maker policy For to design regulation inclusive and equitable development social. The result of this study is about the push involvement active public custom in the planning process development, as well as strengthening protection law to right customs and culture threatened local. The novelty from this study lies in focus integrated analytical focus in the social justiceperspective to phenomenon of the dispossession of the public collective right in the Balik indigeneous community. This research fills in emptiness studies in previous that have not thoroughly examined the social justice in dimension of the context of IKN development and the impact on the existence of local indigeneous communities.